Organocatalytic Enantioselective Approach to Spirocyclic Δβ,γ-Butenolides - Hejmanowska, Joanna; Dzięgielewski, Marek; Kowalczyk, Dorota; Albrecht, Łukasz (My University, 2014)
A novel method for the preparation of the spirocyclic Δβ,γ-butenolides is presented. The developed strategy is based on a trienamine-mediated [4+2]-cycloaddition between (E)-3-alkylidene- 5-arylfuran-2(3H)-ones and 2,4-dienals. Target products containing three contiguous centres including one quaternary are efficiently formed in a highly enantiomerically enriched form in the presence of the silyl-protected diphenylprolinol aminocatalyst.
Keywords: asymmetric synthesis; aminocatalysis; trienamines; Δβ,γ-butenolides; quaternary stereogenic center